Vernacular Architecture of Fort Riley Early 20th Century Postcards - Robert J. Smith (Symphony in the Flint Hills, 2013)
Postcards depicting early 20th Century buildings on Ft. Riley.
Keywords: postcards; Fort Riley; architecture; buildings; history; army; military; George Pond; Quartermaster; Army Cavalry School; Calvary Administration Building; Arnold Hall; Cavalry Stables; Barracks; dorms; sleeping; housing; Main Post Chapel; church; religion; Christian; West Riding Hall; horses